Acquisition of an inheritance entirely by the State Treasury or a local government unit as an inefficient way of expiry of tax liabilities - Olesiak, Jarosław (Studia Iuridica Toruniensia, 2026)
In doctrine and case law, a division is made between effective and ineffective ways of extinguishing tax liabilities. The criterion for this division concerns whether the state or the local authority obtains satisfaction of its claim or whether satisfaction of the claim does not occur. The expiry of a tax liability as a result of the acquisition of the inheritance in its entirety by the State Treasury or a local government unit may appear difficult to qualify in this context. Hence, in the literature, this case is sometimes categorised as an effective, and less frequently as an ineffective, method. However, an analysis of the regulation contained in Article 59 § 1(11) of the Tax Ordinance Act leads to the conclusion that due to the lack of coverage of any part of the tax liability by the inherited assets, we are dealing here with a fully ineffective way of expiry of the tax liability. The tax liability is expired regardless of whether the value of the inherited assets is higher or lower than the amount of the tax liability.